Exercício físico progressivo e equilíbrio ácido-base em sangue capilar - Brandão, Alexandre Fonseca (2010)
The analysis of gases and metabolites in arterial and venous blood reflects the condition of homeostasis of the organism and which instantaneous energy demand required, indicating how biological systems behave in front of some physical stress, including the variation of intensity and volume of physical activity performed. Reactions of these compounds maintenance of constant blood pH by neutralization and / or elimination of organic acids derived from the metabolism momentary. It was an objective method, minimally invasive, to evaluate the acid-base resulting from the progressive increase of physical exercise from 100μL of blood capillary. The methodology used was the Balke protocol for cycle ergometer adapted to the operational needs of the equipment Gas Analyzer Radiometer ABL 800. The progressive increase of the load was 50 by 50 Watts until voluntary exhaustion with collecting and analyzing samples of capillary blood. Volunteers are 13 active students (5 women and 8 men) and three amateur athletes UFSCar aged between 20 and 30 years 25 ± 2, and body mass index 24 ± 4. The results are presented in the acid base nomogram Siggaard-Andersen, developed by the pH values between 7.43 ± 0.02 and 7.35 ± 0.04, ABE (Excess Base Real) between 4.16 ± 1 44 and -7.75 ± 3.17 mmol / L, pCO2 between 35.48 ± 2.61 and 37.20 ± 4.67 mmHg and [HCO3-] between 24 and 17 ± 0.6 ± 2.2 mmol / L with analysis of statistical tools ANOVA and Student's t test. The concentration of gases and metabolites present in blood capillary, presents the characteristic behavior expected during graded exercise as the exponential increase of lactate concentration and pH of the linear decay.